Congenital Deformities of the Hand and Upper Limb - Wang, Wei; Yao, Jianmin (Springer Singapore : Imprint: Springer, 2017)
This book introduces readers to all clinical aspects of congenital anomalies of the hand and upper limb, and offers extensive information on their surgical management, including plastic surgery, pediatric surgery, hand surgery, orthopedic surgery, and general surgery. Drawing on extensive research of related cases, articles and relevant books, and over a thousand pictures of hand deformities, the book addresses the morphology, structure, and defects of hand deformities, while also providing methods for hand examination and hand function assessment. The authors are professors and experts in plastic surgery, hand surgery, and orthopedics from China and the USA, who spent over two years composing and compiling this book.
Keywords: Medicine.; Orthopedics.; Pediatric surgery.; Plastic surgery.; elektronické knihy; electronic books